Eldecalcitol prevents muscle loss and osteoporosis in disuse muscle atrophy via NF-κB signaling in mice - Haichao Zhang; Yanping Du; Wenjing Tang; Minmin Chen; Weijia Yu; Zheng Ke; Shuangshuang Dong; Qun Cheng (Skeletal Muscle, 2023)
Abstract We investigated the effect of eldecalcitol on disuse muscle atrophy. C57BL/6J male mice aged 6 weeks were randomly assigned to control, tail suspension (TS), and TS-eldecalcitol–treated groups and were injected intraperitoneally twice a week with either vehicle (control and TS) or eldecalcitol at 3.5 or 5 ng for 3 weeks. Grip strength and muscle weights of the gastrocnemius (GAS), tibialis anterior (TA), and soleus (SOL) were determined. Oxidative stress was evaluated by malondialdehyde, superoxide dismutase, glutathione peroxidase, and catalase. Bone microarchitecture was analyzed using microcomputed tomography. The effect of eldecalcitol on C2C12 myoblasts was analyzed by measuring myofibrillar protein MHC and the atrophy markers Atrogin-1 and MuRF-1 using immunofluorescence. The influence of eldecalcitol on NF-κB signaling pathway and vitamin D receptor (VDR) was assessed through immunofluorescence, (co)-immunoprecipitation, and VDR knockdown studies. Eldecalcitol increased grip strength (P < 0.01) and restored muscle loss in GAS, TA, and SOL (P < 0.05 to P < 0.001) induced by TS. An improvement was noted in bone mineral density and bone architecture in the eldecalcitol group. The impaired oxidative defense system was restored by eldecalcitol (P < 0.05 to P < 0.01 vs. TS). Eldecalcitol (10 nM) significantly inhibited the expression of MuRF-1 (P < 0.001) and Atrogin-1 (P < 0.01), increased the diameter of myotubes (P < 0.05), inhibited the expression of P65 and P52 components of NF-κB and P65 nuclear location, thereby inhibiting NF-κB signaling. Eldecalcitol promoted VDR binding to P65 and P52. VDR signaling is required for eldecalcitol-mediated anti-atrophy effects. In conclusion, eldecalcitol exerted its beneficial effects on disuse-induced muscle atrophy via NF-κB inhibition.